Prevalence, phenotypic characteristics and prognostic role of apparent treatment resistant hypertension in the German Chronic Kidney Disease (GCKD) study - Mielke, Johanna; Trucks-Jansen, Holger; Schurmann, Claudia; Kotsis, Fruzsina; Koettgen, Anna; Schneider, Markus; Eckardt, Kai-Uwe; Freitag, Daniel F.; Eitner, Frank; Becker, Michael S. (Journal of Human Hypertension, 2022)
Treatment resistant hypertension (TRH) appears of particular relevance in patients with chronic kidney disease (CKD). However, causes and consequences of TRH in CKD patients remain incompletely understood. Therefore, we analyzed the prevalence of apparent TRH (aTRH), and phenotypic characteristics and prognosis associated with aTRH among participants of the German Chronic Kidney Disease (GCKD) study. As insufficient medication adherence has been shown to be a frequent cause of pseudoresistance, we also assessed treatment adherence. Study participants were classified as having aTRH, controlled hypertension and uncontrolled hypertension based on study visit blood pressure and self-reported medication intake. Drug adherence was assessed by comparing self-reported antihypertensive medication with detectable urinary drug metabolites measured by mass spectroscopy. Out of 4901 individuals included in this study, 38% were classified as having aTRH. Male sex, older age, lower estimated glomerular filtration rate (eGFR), higher body mass index (BMI), higher urine albumin-to-creatinine ratio (UACR) and presence of diabetes mellitus were independently associated with higher prevalence of aTRH in a multivariable adjusted regression model. Patients classified as aTRH had higher risk for major adverse cardiovascular events and worsening of kidney disease compared to patients with no aTRH after multivariate adjustment for potential confounders. There was a high agreement between self-reported medication and detectable urinary drug metabolites. In conclusion, in a cohort of Caucasian patients with moderately severe CKD, aTRH was highly prevalent and, in most cases, likely not caused by low medication adherence. Furthermore, aTRH was linked to cardio-renal endpoints, emphasizing the need for improved management.
CRIS-Team WoS Importer:2022-05-20